Ovarian Malignant Brenner Tumor - Romi Alfianto; Alphania Rahniayu; Indra Yuliati (Majalah Obstetri dan Ginekologi, 2018)
Objectives: To report one malignant Brenner tumor (MBT) case in Dr. Soetomo Hospital, Surabaya, Indonesia, that underwent therapy from August 2016 to August 2017.Case report: A woman aged 62 years underwent total abdominal hysterectomy and bilateral salphingo-oophorectomy surgery with histopathologic results of malignant Brenner Tumor. From immunohistochemical examination the expression of p63 was positive. The patient had been treated with Paclitaxel carboplatin chemotherapy for 5-cycles, with the results of the last post-chemotherapy evaluation showing no recidive mass.Conclusion:There was only one case of malignant ovarian Brenner Tumor in Dr Soetomo Hospital, Surabaya, Indonesia, in 2014- 2016. The diagnosis can only be based on anatomic pathology examination. The specific tumor markers for malignant Brenner tumors have so far not been found.